Does globalization create superstars? - Hans Gersbach; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2007)
To examine the impact of globalization on managerial compensation, we consider a matching model where a number of firms compete both in the product market and in the managerial market. We show that globalization, i.e. the simultaneous integration of product markets and managerial pools, leads to an increase in the heterogeneity of managerial salaries. Typically, while the most able managers obtain a wage increase, less able managers are faced with a reduction in wages. Hence our model can explain the increasing heterogeneity of CEO compensation that has been observed in the last few decades.
Keywords: D43; F15; J31; L13; 330; globalization; manager remuneration; superstars; Globalisierung; Führungskräfte; Leistungsentgelt; Wirtschaftsmodell